SPEECH COMMUNICATION IN CLOSE LANGUAGE CONTACTS - Makhmadieva Rano Said-Abdullaevna; Zhalolova Nasiba Bakhromzhon kizi (American Journals, 2024)
This article examines modern scientific achievements in the field of the theory of bilingualism, which grew on the basis of language contacts, and also examines the leading aspects of bilingualism - linguistic, psychological, pedagogical.
Keywords: Speech communication, multilingualism, mass communication, bilingualism, theory, aspects, science, achievements.